Clinical profile of acute kidney injury in neonatal sepsis and perinatal asphyxia using nRIFLE and modified KDIGO criteria - Subramanian, Sharan; Malik, Sushma; Wade, Poonam Abhay (Indian Journal of Child Health, 2019)
Background: Newborn babies with sepsis and perinatal asphyxia form a high-risk group for developing neonatal acute kidney injury (nAKI). The diagnosis and staging of nAKI is challenging and has several limitations. Objective: The objectives of this study were to estimate the hospital-based incidence of nAKI in septic and asphyxiated neonates, describe their clinical profile and outcome, and compare the two classifications – neonatal risk, injury, failure, loss, and end-stage renal disease (nRIFLE) and neonatal modified Kidney Disease: Improving Global Outcomes (KDIGO) criteria for their agreement. Materials and Methods: Consecutive neonates who fulfilled the diagnosis of sepsis or perinatal asphyxia were included in this prospective cohort study. Urine output was monitored 6 hourly by diaper weight and serum creatinine every 48 h or earlier if required. The clinical profile and outcome of neonates who developed AKI were studied, and AKI was staged using both nRIFLE and KDIGO criteria. Chi-square test was used to test the association of risk factors with AKI, Pearson’s Chi-square and Kappa statistics were used to compare the two staging criteria. Results: Of 90 neonates enrolled, the incidence of AKI in sepsis was 145/1000 neonates and perinatal asphyxia was 464/1000 neonates. AKI was maximally observed in the early preterm neonates (45.4%) and very low birth weight neonates (36.36%). Oliguria was present in a majority of the neonates with nAKI but varied according to the classification system used. nAKI was significantly associated with high mortality (54.2%) (p<0.01) which increased with decreasing gestation and birth weight and increasing severity of nAKI. On comparing KDIGO and nRIFLE criteria, there was a poor agreement between the two. Conclusion: AKI is a common occurrence in septic and asphyxiated neonates and portends poor outcomes. Although studies have evaluated nRIFLE and KDIGO individually, larger studies comparing the two criteria are required to improve early diagnosis and accurate staging of neonatal AKI.